The effectiveness of warm water compresses in reducing gout pain - Joice Mangngemba Andika Putri; Suprapto Suprapto; Darmi Arda; Maria Kurni Menga (Edukasi Ilmiah Indonesia, 2024)
Introduction: Gout is caused by the accumulation of uric acid in the body's joints. When there is excess uric acid in the bloodstream and more than can be excreted, the uric acid seeps into the joint tissue, causing pain and swelling. Pain is the most frequent symptom of Gout. The triggering factor that can cause gout is excessive consumption of foods that contain purines. One of the signs and symptoms that people with gout arthritis can feel is pain in the joints, such as in the big toe, wrist joint, foot joint, knee joint, and elbow joint. This study aims to determine the effectiveness of warm water compresses to reduce gout pain. Methods: A qualitative study with a case study approach focused on the effectiveness of warm compresses to reduce gout pain was conducted in 2 patients. Results showed a decreased pain scale after being given warm water compress therapy in patients with gout or gout arthritis. When the results were obtained before the warm water compress therapy, Respondent One experienced a pain scale of 6 and Respondent 2 had a pain scale of 5 after being given warm water compress therapy; the pain scale felt by Respondent 1 was on the pain scale four and respondent two on the pain scale 3. Conclusions: Providing warm water compress therapy to respondents with gout pain or Gout Arthritis reduces the pain scale because warm water compresses are performed. It is hoped that it will be a source of information for the community in dealing with gout pain. In addition, it can also increase the community's insight into maintaining lifestyles, such as diet and the environment, to maintain body health and develop knowledge and skills in providing good nursing care, especially in homecare activities.